From Somali to Bahasa Indonesia: A Narrative Case Study on Language Policy and the Lived Linguistic Experience of a Somali Student in Indonesia: Dari Somalia ke Bahasa Indonesia: Studi Kasus Naratif tentang Kebijakan Bahasa dan Pengalaman Linguistik Mahasiswa Somalia di Indonesia - Sabiru Salihu; Farikah Farikah; Wahida Wahyuni (Universitas Tidar, 2025)
Indonesia's growing English-Medium Instruction (EMI) policy and vibrant multilingual landscape attract international students, yet the linguistic experiences of African students remain significantly under-researched. This narrative inquiry explored how Somali students in Indonesia perceive and navigate their linguistic experiences while enrolled in EMI programs, and what narratives emerge that illuminate the broader implications of language policy and multicultural education in Indonesia. A single Somali undergraduate participant was selected, and data were collected through in-depth semi-structured interviews, a life story approach, and observational notes. The data were analyzed using thematic narrative analysis. Key findings revealed profound language shock and initial identity displacement, strategic translanguaging and technological mediation, the vital role of peer-mediated emotional and linguistic support, and the cultivation of resilience alongside an evolving learner identity. These insights underscore the necessity for more robust pre-arrival language support, formalized peer mentoring programs, and targeted lecturer training to bridge the gap between EMI policy and practice. This study contributes to a nuanced understanding of language policy's lived implications and offers practical recommendations for enhancing international student inclusion in diverse educational contexts.